2008
DOI: 10.1002/hyp.7034
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resolution and topographic uncertainty on melt modelling using hypsometric sub‐grid parameterization

Abstract: Modelling of physical processes such as ablation or runoff at continental or global scales provides a key challenge: a high degree of abstraction is required in order to minimize computational demands, while spatial and temporal variability of key processes, often at the sub‐scale level, need to be adequately captured and reproduced within a lower resolution model. For some approaches, such as temperature index models, downscaling to lower resolutions is straightforward. However a key issue when using these do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, subgrid parameterisation for the calculation of ablation/accumulation has been shown to be effective in compensating for dependencies on scale while incurring only a small additional computational cost (Hebeler and Purves, 2008b;Marshall and Clark, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, subgrid parameterisation for the calculation of ablation/accumulation has been shown to be effective in compensating for dependencies on scale while incurring only a small additional computational cost (Hebeler and Purves, 2008b;Marshall and Clark, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This indicafed that the model sensitivity increases with the discretization level since the inclusion of additional processes brings with it additional parameters and data input. Hebeler & Purves (2008) assessed the impact of scaling on models from differenf resolution, and concluded that tested models had clear dependencies on scale, terrain roughness and variations of parameter thresholds. Bogena et al (2005) focused on model uncertainty analysis in the simulation of groundwater recharge at different scales.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, choosing an appropriate resolution is a key task in hydrology (Hebeler & Purves 2008). The scaling dilemma exists when approaching better model performance with higher resolution data: the limited effect to bring more accurate results after a certain resolution threshold and the massive demand of storage capacity and computer time required by high resolved data (Vazquez et al 2002;Omer et al 2003;Cullmann et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The most straightfo rward extension is the incorporation of global radiation measureme nts which distribute melt in space according to local factors of aspect and account for varying solar position [9,10,36,12,32,24 ,13,28] . Further research has tried to include the evolution of snow density and snow cover albedo over the melt season [4,50,49,11,41,20 ]. This seasonality can also be emulated with time-varying snowmelt factors, e.g.…”
Section: Introductionmentioning
confidence: 99%